Criminal justice profiling and EU data protection law: precarious protection from predictive policing. Issue 2 (June 2019) - Lynskey, Orla
Abstract: This paper examines the application of the latest iterations of EU data protection law – in the General Data Protection Regulation, the Law Enforcement Directive and the jurisprudence of the Court of Justice of the EU – to the use of predictive policing technologies. It suggests that the protection offered by this legal framework to those impacted by predictive policing technologies is, at best, precarious. Whether predictive policing technologies fall within the scope of the data protection rules is uncertain, even in light of the expansive interpretation of these rules by the Court of Justice of the EU. Such a determination would require a context-specific assessment that individuals will be ill-placed to conduct. Moreover, even should the rules apply, the substantive protection offered by the prohibition against automated decision-making can be easily sidestepped and is subject to significant caveats. Again, this points to the conclusion that the protection offered by this framework may be more illusory than real. This being so, there are some fundamental questions to be answered – including the question of whether we should be building predictive policing technologies at all.